Did the Health Card Program Ensure Access to Medical Care for the Poor during Indonesia’s Economic Crisis? - Pradhan, Menno; Saadah, Fadia; Sparrow, Robert (World Bank, 2012)
The Indonesian Social Safety Net health card program was implemented in response to the economic crisis that hit Indonesia in 1997, to preserve access to health care services for the poor. Health cards were allocated to poor households, entitling them to subsidized care from public health care providers. The providers received budgetary support to compensate for the extra demand. This article focuses on the effect of the program on primary outpatient health care use, disentangling the direct effect of allocating health cards from the indirect effect of government transfers to health care facilities. For poor health card owners the program resulted in a net increase in use of outpatient care, while for nonpoor health card owners the program resulted mainly in a substitution from private to public health care. The largest effect of the program seems to have come from a general increase in the supply of public services resulting from the budgetary support to public providers. These benefits seem to have been captured mainly by the nonpoor. As a result, most of the benefits of the health card program went to the nonpoor, even though distribution of the health cards was propoor. The results suggest that had the program, in addition to targeting the poor, established a closer link between provision of services to the target groups and funding, the overall results would have been more propoor.